Organic Agriculture 3.0 is innovation with research - Rahmann, Gerold; Ardakani, M. Reza; Bàrberi, Paolo; Boehm, Herwart; Canali, Stefano; Chander, Mahesh; David, Wahyudi; Dengel, Lucas; Erisman, Jan Willem; Galvis-Martinez, Ana C.; Hamm, Ulrich; Kahl, Johannes; et al. (Springer, 2017)
Organic agriculture can and should play an important role in solving future challenges in producing food. The low level of external inputs combined with knowledge on sustainablity minimizes environmental contamination and can help to produce more food for more people without negatively impacting our environment. Organic agriculture not only includes farming as a production practice but it also includes processing, trade and consumption. Nevertheless, Organic agriculture must always evolve to overcome emerging challenges. Science-based knowledge attained through dedicated research is required to strengthen organic food and farming as a means to solve future challenges. In 2010, a global discussion about Organic 3.0 was initiated to address current problems our agri-food systems are facing. Many scientifically and practically proven results are already available to make organic agriculture a strong tool to solve some of these challenges. However, the organic agri-food system has to be developed further to fulfill its potential. The contribution of organic agriculture to help solve current problems linked to food security and environmental quality was discussed during the International Society of Organic Agricultural Research (ISOFAR) Symposium BOrganic 3.0 is Innovation with Research^, held September 20–22, 2015, in conjunction with the first ISOFAR International Organic Expo, in Goesan County, Republic of Korea. Some of the world’s most active scientists in organic agriculture attended the symposium. This paper is a result of their discussions and aims to give an overview of research conducted and required to strengthen organic agriculture in its ambitions to overcome agronomic challenges, contribute to food security and protect our common environment.
Keywords: organic 3.0; agri-ecology; ISOFAR; ecological intensification; organic agriculture; global food systems; organic farming research; organic food challenges